2018
DOI: 10.33552/wjovr.2018.01.000504
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Eye and Vision Problems among Rural Egyptians Preschooler

Abstract: Objectives:The aim of this study was to determine the prevalence of visual impairment and percent distribution of childhood diseases affecting vision among preschool children (one day to 6 years) in Giza governorates of Egypt as a first step in National survey.Methods: A population-based survey was conducted on a multistage cluster sampling. Target population was one day to 6 years children living in rural areas of Giza, governorate using systematic random samples based on birth records. The total sample of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Their study reported RE as the most common condition, while this study in it is the fourth most common condition. 30 The pattern of ocular diseases between the genders showed some variation in this study and the overall finding that boys appear to be disproportionally affected supports the results of a study conducted by Demissie et al 31 Gender variations in ocular health are clinically under-addressed. 32 Although there are evidence of gender disparities with regard to some ocular diseases prevalent for adult women more than men related to some biological and cultural factors, there are no available data in regard to younger children.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Their study reported RE as the most common condition, while this study in it is the fourth most common condition. 30 The pattern of ocular diseases between the genders showed some variation in this study and the overall finding that boys appear to be disproportionally affected supports the results of a study conducted by Demissie et al 31 Gender variations in ocular health are clinically under-addressed. 32 Although there are evidence of gender disparities with regard to some ocular diseases prevalent for adult women more than men related to some biological and cultural factors, there are no available data in regard to younger children.…”
Section: Resultssupporting
confidence: 88%
“…The pattern of ocular diseases in this study is similar to what was reported in a study conducted among Egyptian pre‐school children in rural areas, with one exception. Their study reported RE as the most common condition, while this study in it is the fourth most common condition 30 …”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Their study found the highest percentage of ocular morbidity was refractive errors, unlike in this study where it was the third in order. Otherwise their study was matching the nding of this research [10] .…”
Section: Discussionmentioning
confidence: 94%